Using genetic algorithm for solving N-Queens problem - Turky A.M.; Ahmad M.S. (2023)
The N-Queens problem is a well-known NP-Hard problem. Optimal solutions to small N values can be found in reasonable time by classical search algorithms or linear programming. However, since the N-Queens problem is a constraint satisfaction problem (CSP), it will be very time consuming to solve larger N values with guaranteed optimality. In this paper, genetic algorithm was adopted to solve the N-Queens problem. Results show that this evolutionary approach is very efficient and able to produce good results compared with other approaches e.g. classical search algorithms or linear programming. 2010 IEEE.